Flora do Espírito Santo: gêneros Alicia, Amorimia, Barnebya, Bunchosia, Carolus, Dicella, Heladena, Hiraea, Lophopterys, Mascagnia, Mezia, Niedenzuella, Tetrapterys e Thryallis (Malpighiaceae) - Barros, Paulo Henrique Dettmann (2019)
The state of Espírito Santo is fully inserted in the Atlantic Forest, which is considered one of the most diverse biogeographic zones and most at risk with the fragmentation of natural areas. The flora of the state of Espírito Santo is still poorly studied and in recent studies its richness has been increasingly revealed. This work follows a series of studies focused on the taxonomy of Malpighiaceae in the state of Espírito Santo, presenting the taxonomic treatment of 14 genera. This study aims to expand the taxonomic knowledge of genera for the state, show the geographical distribution of species, make descriptions, identification keys and illustrations of species. Through material analysis, 26 species were found in herbariums and field expeditions that took place between January 2018 to April 2019, from the studied genera the largest was Tetrapterys (4 spp.) followed by Bunchosia, Hiraea, Mascagnia e Niedenzuella (3 spp. each), Dicella (2 spp.), Alicia, Amorimia, Barnebya, Carolus, Heladena, Lophopterys, Mezia e Thryallis (1 sp. each), among the species found there were two new occurrences for the state Hiraea macrophylla and H. restingae, both known only for the state of Rio de Janeiro.   No presente trabalho propõe-se uma visão metaética sobre a Teoria dos Sistemas Sociais Comunicativos Autorreferenciais de Niklas Luhmann na qual busca-se identificar sobre quais condições é possível a ocorrer a reconstrução normativa nos sistemas sociais. Em sistemas que operam em um ambiente de complexidade infinita, criando complexidade interna para serem capazes de processar e reduzir a complexidade externa como condição de operabilidade, a reconstrução normativa torna-se condição de continuidade sistêmica. Sistemas que não conseguem, no processo de formação de juízos de valor para construir sentido, controlar o conteúdo das crenças justificadoras desses juízos morais, permitindo, inclusive, sua alteração, não possuem continuidade num ambiente de crescente complexidade. Neste contexto, a autorreferência é a condição para que ocorra a reconstrução normativa nos sistemas sociais, capaz de permitir, na formação dos juízos de valor, que suas crenças justificadoras, sejam dadas como problema, No presente trabalho propõe-se uma visão metaética sobre a Teoria dos Sistemas Sociais Comunicativos Autorreferenciais de Niklas Luhmann na qual busca-se identificar sobre quais condições é possível a ocorrer a reconstrução normativa nos sistemas sociais. Em sistemas que operam em um ambiente de complexidade infinita, criando complexidade interna para serem capazes de processar e reduzir a complexidade externa como condição de operabilidade, a reconstrução normativa torna-se condição de continuidade sistêmica. Sistemas que não conseguem, no processo de formação de juízos de valor para construir sentido, controlar o conteúdo das crenças justificadoras desses juízos morais, permitindo, inclusive, sua alteração, não possuem continuidade num ambiente de crescente complexidade. Neste contexto, a autorreferência é a condição para que ocorra a reconstrução normativa nos sistemas sociais, capaz de permitir, na formação dos juízos de valor, que suas crenças justificadoras, sejam dadas como problema, permitindo um controle sobre o conteúdo moral por meio da perspectividade.   In the present work it is proposed a metahetical view on Niklas Luhmann's Theory of Self-Referential Communicative Social Systems in which it is sought to identify on which conditions it is possible to occur the normative reconstruction in social systems. As systems operate in an environment of infinite complexity, creating internal complexity to be able to process and reduce external complexity as a condition of operability, normative reconstruction becomes a condition of systemic continuity. Systems that cannot, in the process of forming value judgments to construct meaning, control the content of the justifying beliefs of these moral judgments, even allowing their alteration, do not have conditions of continuity in an increasingly complex environment. In this context, self-referencing is the condition for normative reconstruction in social systems, capable of allowing, in the formation of value judgments, that their justifying beliefs be given as a problem, allowing a control over moral content through perceptivity.